2009
DOI: 10.1007/s12105-009-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Oral Cavity: Clinicopathologic and Immunohistochemical Study of 21 Cases

Abstract: We describe clinical, morphologic, and immunohistochemical features of 21 cases of solitary fibrous tumor presenting in the oral cavity. There were 9 male and 12 female patients with a median age of 51 years (range 37–83). The most common locations included the buccal mucosa (the most common site), lip, maxillary or mandibular vestibule and tongue. Histopathologic examination showed well-circumscribed tumors with two well-defined patterns: the classic pattern with densely cellular areas alternating with hypoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 61 publications
(74 reference statements)
2
59
1
5
Order By: Relevance
“…Anti-CD34 antibody, which recognizes a 110-kDa transmembrane cell surface glycoprotein found on myeloid progenitor cells, is the most consistent and reliable immunohistochemical marker for SFT [14][15][16]. On the other hand, neoplastic cells are negative for cytokeratins, S-100 protein, epithelial membrane antigen, smooth muscle actin, and Factor VIII [13,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anti-CD34 antibody, which recognizes a 110-kDa transmembrane cell surface glycoprotein found on myeloid progenitor cells, is the most consistent and reliable immunohistochemical marker for SFT [14][15][16]. On the other hand, neoplastic cells are negative for cytokeratins, S-100 protein, epithelial membrane antigen, smooth muscle actin, and Factor VIII [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…Given the wide range of morphology, SFT can potentially be mistaken for other benign and malignant soft tissue tumors [7,12,14,16]. The differential diagnosis of benign SFT involving the oral cavity includes a variety of lesions, especially fibrous histiocytoma, schwannoma, and, most importantly, hemangiopericytoma [14,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that 13-23% of the pleural SFT are malignant [5]. In contrast, intraoral SFT, has an excellent prognosis associated with a benign clinical behavior [8].…”
Section: Discussionmentioning
confidence: 99%